2016
DOI: 10.1242/jcs.184663
|View full text |Cite
|
Sign up to set email alerts
|

Basolateral sorting and transcytosis define the Cu+-regulated translocation of ATP7B to the bile canaliculus

Abstract: The Cu + pump ATP7B plays an irreplaceable role in the elimination of excess Cu + by the hepatocyte into the bile. The trafficking and site of action of ATP7B are subjects of controversy. One current proposal is that an increase in intracellular Cu + results in the translocation of ATP7B to the lysosomes and excretion of excess Cu + through lysosomal-mediated exocytosis at the bile canaliculus. Here, we show that ATP7B is transported from the trans-Golgi network (TGN) to the bile canaliculus by basolateral sor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 42 publications
2
22
0
Order By: Relevance
“…Copper-treatment resulted in reduced ATP7B colocalization with Golgin-97 ( Figure 4B) and its appearance at the ZO-1-bordered canaliculi ( Figure 4C-D). ATP7B in copper-treated hiHeps also appeared at LAMP1positive compartments ( Figure 4E), which have been implicated in the trafficking of ATP7B to the bile canaliculi [12,23] although debated [34]. Fluorescence intensity boxplots covering the intracellular ATP7B compartments and the canalicular domain illustrated ATP7B translocation by the appearance of overlapping ABCC2 and ATP7B peaks in the copper-treated conditions ( Figure 4F).…”
Section: Polarized Hiheps Recapitulate Polarized Trafficking Processesmentioning
confidence: 96%
“…Copper-treatment resulted in reduced ATP7B colocalization with Golgin-97 ( Figure 4B) and its appearance at the ZO-1-bordered canaliculi ( Figure 4C-D). ATP7B in copper-treated hiHeps also appeared at LAMP1positive compartments ( Figure 4E), which have been implicated in the trafficking of ATP7B to the bile canaliculi [12,23] although debated [34]. Fluorescence intensity boxplots covering the intracellular ATP7B compartments and the canalicular domain illustrated ATP7B translocation by the appearance of overlapping ABCC2 and ATP7B peaks in the copper-treated conditions ( Figure 4F).…”
Section: Polarized Hiheps Recapitulate Polarized Trafficking Processesmentioning
confidence: 96%
“…Recent studies in hepatic HepG2 cells, in human hepatocytes and in mouse liver tissue indicate that ATP7B vesicles belong to the late endosomal (LE)/lysosomal compartments [21,33,34]. In contrast, other reports suggest that ATP7B moves from the Golgi to early endosomes in Can10 and WIF-B hepatic cells [35,36].…”
Section: Atp7b 'Vesicles'mentioning
confidence: 98%
“…A different and quite surprising mechanism of ATP7B delivery to the apical domain of hepatocytes has been recently proposed by Lalioti et al . , who provided evidence showing transcytosis of ATP7B from the basolateral to the apical surface of polarized Can10 cells. However, these findings appear to be in conflict with the rest of the existing data on ATP7B trafficking.…”
Section: Final Destination Of Atp7bmentioning
confidence: 99%
“…ii) The results of CFTR mutagenesis and siRNA screens showed that transcytosis of CFTR in CFBE is independent of N-glycans, AP-1B, Rab3b, Rab17, Rab25 or the exocyst complex that are essential for the apical transcytosis of pIgR, TfR and FcRn (Hunziker and Peters, 1998;Nelms et al, 2017;Perez Bay et al, 2014;Tzaban et al, 2009;van et al, 2002). iii) Finally, transcytotic CFTR seems to avoid the CRE and ARE compartments that are commonly used by other transcytotic cargoes (Jerdeva et al, 2010;Lalioti et al, 2016). Interestingly, constitutive TfR apical transcytosis in AP-1B-expressing MDCK or CFBE (Figures S3C-E and S4H) also avoids the Rab11 + ARE, similar to that of FcRn (Tzaban et al, 2009).…”
Section: Discussionmentioning
confidence: 85%